The Land Mollusca of St. Croix, Virgin Islands - Morris K. Jacobson (Hello World!, 1968)
The present compilation has various sources. These include the personal collections of the author together with those made by Gordon Usticke and George A. Seaman, inhabitants of St. Croix. The largest single source is the collection of St. Croix material in the MCZ, from which most locality records were taken. This rich collection contains, besides much material supplied by Mr. Seaman, also numerous lots sent by Harry A. Beatty who collected on St. Croix from 1938 to 1945.